Non finito. Opera interrotta e modernità - Dolfi, Anna (Moderna/Comparata, 2015)
Unfinished work or interrupted work... It is difficult to find a definition, to identify the theme, to distinguish chance from intentionality. Few 'genres' and / or variations express as the 'unfinished' the same need for what is external to the work and which somehow completes it, bringing the work in a privileged position to create a harmony with our restless modernity. No wonder that in literature, in addition to what has been brutally interrupted, the letters, the diaries, the chronicles of disease and suffering are naturally suspended works. No wonder either that incompleteness accompanies the writings referring to unsolved issues, hidden traumas, silent melancholy. Dictated by choice or by distinct degrees of incapacity, the temptation of the unfinished pursues, urges, deludes its author... The private writings, the sketches, the projects, the papers testify the path necessary for the work to develop and conquer its shape. This book is rich and suggestive and has been conceived and edited by Anna Dolfi. Like its very object, the work is drafted in the perspective of the unfinished and questions some of the many possible examples, along a diachronic arc that goes to literature at figurative arts, theatre, cinema: from Leonardo to Blake, from Ariosto to Stendhal, from Dossi to Gadda, from Kafka to Borges, from Sarraute to Morante, from unknown writers affected by 'cancroregina' to the last Pirandello staged by Tiezzi, up to Fellini of the impossible Mastorna ... At the centre of the volume the readers will find a section with the typescript pages and the unpublished notebooks of / for the work La scelta by Giuseppe Dessí. They lead to the limits of white space, where the chambre claire fixes what is hidden beyond the writing with few, rarefied signs.